The potential roles of type I interferon activated neutrophils and neutrophil extracellular traps (NETs) in the pathogenesis of primary Sjögren’s syndrome - Peng, Yu; Wu, Xunyao; Zhang, Shulan; Deng, Chuiwen; Zhao, Lidan; Wang, Mu; Wu, Qingjun; Yang, Huaxia; Zhou, Jiaxin; Peng, Linyi; Luo, Xuan; Chen, Yingying; et al. (Arthritis research & therapy, 2022)
Objective Neutrophils and aberrant NETosis have been implicated in the pathogenesis of diverse autoimmune diseases; however, their roles in primary Sjögren's syndrome (pSS) remain unclear. We aimed to reveal the potential roles of neutrophils and neutrophil extracellular traps (NETs) in pSS. Methods pSS patients were enrolled and NETosis markers were measured in plasma and labial glands using ELISA and immunofluorescence. The gene signatures of neutrophils were assessed by RNA-Seq and RT-PCR. Reactive oxygen species (ROS), mitochondrial ROS (MitoSOX) production, and JC-1 were measured by flow cytometry. Results NETosis markers including cell-free DNA (cf-DNA) and myeloperoxidase (MPO) in plasma and labial glands from pSS patients were significantly higher than healthy controls (HCs) and were associated with disease activity. RNA sequencing and RT-qPCR revealed activated type I IFN signaling pathway and higher expression of genes related to type I interferon in pSS neutrophils. Further stimulating with IFN-[alpha] 2a in vitro significantly induced ROS production and JC-1 monomer percentage in pSS neutrophils. Conclusions Our data suggest the involvement of neutrophils and enhanced NETosis in pSS patients. Further mechanism study in vitro revealed that type I IFN activation in pSS neutrophils led to mitochondrial damage and related ROS production which finally result in the generation of NETs. Keywords: Primary Sjögren's syndrome, Neutrophils, Neutrophil extracellular traps, Type I interferon, Mitochondrial damage